Marketing of Banking Financial Services Products: Islamic Principles and Values - Sutikno Sutikno; Mery Ramadani; Alda Faujan (Akademi Sertifikasi Profesi Internasional, 2024)
Ethical marketing management of banking financial services products in accordance with Islamic principles and values. This paper is divided into several parts, first: explaining what marketing means, the scope and importance of marketing in business. The second part: discusses how marketing management ethics in Islam, the third part explains what is the difference between sharia and conventional marketing. The last discussion is about how Islamic ethics and values are applied in the marketing management of banking service products. There are several things that are noted in the discussion of this article, the practice of applying ethics in banking companies will always benefit the company both in the medium and long term. In addition, it can also increase crew motivation, protect the principle of free trade and increase competitive advantage. The overall strategy management that has been made based on ethics will run successfully, according to the plan, if the marketing parties consistently carry out the strategy that has been implemented, and review the marketing strategy that has been carried out if it is not successful in the business